From Doubt to Diagnosis: Canadian Patient Perspectives on a Limb‐Girdle Muscular Dystrophy Diagnosis. - Osman, Homira; Adamji, Zainab; Pfeffer, Gerald; Warman‐Chardon, Jodi; Varma, Pryamvada; Keindel, Jenna; Lintern, Stacey (Health Expectations, 2025)
Introduction: Limb‐girdle muscular dystrophies (LGMDs) encompass a rare and genetically diverse set of disorders, posing challenges in diagnosis due to the absence of distinct pathological features, leading to frequent misdiagnoses and inadequate symptom management. Yet, there is a scarcity of published data on how patients perceive the diagnostic journey of LGMD. Our aim was to unveil the firsthand experiences of individuals with LGMD to gain insight into their perspective on the diagnosis process. This study comprehensively captures the LGMD patient and caregiver experiences—from symptom onset through diagnosis to current disorder management. Methods: Insights into the lived experience of LGMD were consolidated from semi‐structured interviews and a cross‐sectional mixed‐methods survey of quantitative and qualitative questions. Quantitative data were analysed using descriptive statistics and frequencies, while inductive content analysis was applied to qualitative responses. During the validation phase, patient authors validated and prioritised the insights and overarching themes. Results: From 108 participants (104 people with LGMD and 4 parent caregivers), five overarching themes were identified. These themes include (1) difficulty with diagnostic process, with 8 years noted as time from the symptom onset until they obtain the definitive diagnosis; (2) difficulty obtaining genetic testing and specialist care; (3) sense of disconnect with healthcare professionals, often resulting from lack of knowledge and awareness of the condition; (4) a state of emotional distress, feelings of hopelessness, depression, fear and anxiety with the diagnosis process; and (5) impact on mobility and ambulation. Conclusion: The LGMD diagnosis journey is marked by barriers and misdiagnoses, leading to considerable diagnostic delays. Overcoming these challenges requires increased awareness among healthcare professionals and improved patient access to genetic testing. Patient or Public Contribution: Patients with LGMD were involved as research partners in all phases of this study, including identifying the research question and the need for an assessment of the diagnosis journey for LGMD in Canada. The patients also worked with the authors to interpret and validate the data collected and contributed to the preparation of the manuscript by participating in the review and editing process.